The decision making method of task arrangement based on analytic hierarchy process for nuclear safety in radiation field. (November 2016) - Li, Meng-kun; Liu, Yong-kuo; Peng, Min-jun; Xie, Chun-li; Yang, Li-qun
Abstract: Unstructured and multi-objective task arrangement in radiation field is a complicating problem decision-makers are most concerned about. Proper task arrangement is helpful to improve efficiency of engineering and reduce hazard. The goal of this work is to discuss some criteria of task, build task hierarchy structure model, and then propose a task analytic method in radiation field based on analytic hierarchy process (AHP). The proposed method is useful for selection of schemes to reduce hazard and increase efficiency of task. In addition, we use this proposed method solve a hypothetical case, which is utilized to explain how the method works and to prove the method effective. Highlights: Task estimation in radiation field is a multiple-attributes problem. Task analytic hierarchy method based on AHP is proposed. Scheme of task is analyzed based on various attitudes and criteria. Methodology and virtual simulation are combined to technical support for nuclear safety.